Isavuconazole: an orphan drug for treating invasive candidiasis. (3rd March 2016) - Aigner, Maria; Chandorkar, Parul; Mutschlechner, Wolfgang; Lass-Flörl, Cornelia
Abstract: Introduction : Infections by Candida species are the most frequent invasive fungal infections in critically ill patients, and available licensed antifungals are restricted and show several limitations such as a narrow spectrum of activity, toxicity, and drug interactions. Hence, there is an urgent need for new antifungal drugs with favorable pharmacokinetic (PK), improved efficacy and safety profile. Isavuconazole is new broad-spectrum antifungal available as an oral and intravenous formulation; the prodrug isavuconazonium sulfate (BAL8557) is a water-soluble triazole and its active moiety, BAL4815, is a potent inhibitor of ergosterol biosynthesis. Isavuconazole offers several advantages over other azole antifungals, including high prodrug water solubility, high oral bioavailability, predictable and linear PK with no relevant food effect. As with other azoles, a loading dose is required. Areas covered : Studies and reviews were collected through a MEDLINE search and fromhttp://www.clinicaltrials.gov, Food and Drug Administration briefing documents, program abstracts from international symposia, and the manufacturer's website with focus on isavuconazole and Candida spp. Expert opinion : Clinical data regarding isavuconazole and outcome of Candida infections are limited, hence a clear position of the drug in any treatment-regimens are still open; the results of the ACTIVE-study showed that isavuconazole did not meet the primary objective of demonstrating non-inferior efficacy of isavuconazole versus caspofungin at the end of iv therapy.